Effects of Growth Hormone Replacement on Peripheral Muscle and Exercise Capacity in Severe Growth Hormone Deficiency - Gonzalez, Susana; Sathyapalan, Thozhukat; Javed, Zeeshan; Atkin, Stephen L. (Frontiers in Endocrinology, 2018)
Objective To evaluate the effect of growth hormone therapy (rGH) on mitochondrial function on peripheral muscle and to correlate with exercise capacity in subjects with severe adult growth hormone deficiency (GHD) . Design Six months, double blind, randomised, cross over, placebo controlled trial of subcutaneous rGH in 17 patients with GHD. Measurements Quadriceps muscle biopsies were obtained at baseline, 3 and 6 months to measure succinate dehydrogenase (SDH) to assess mitochondrial activity. Exercise capacity was measured with cardiopulmonary exercise testing. Lipids, glycaemic parameters and body fat levels were also measured. Results IGF1 levels normalised with rGH in the active phase (p<0.005) with a reduction in total body fat (36.2±10.4% vs 37.6±10.7%, p<0.05). Patients showed an increase in SDH (P<0.01) from base line that differed between placebo and rGH therapy treatment groups (P<0.05): those treated by rGH followed by placebo showed a significant rise in SDH (p<0.001) followed by a fall, with a significant between group difference at the end of 6 months (p<0.05). No significant improvements or correlation with exercise capacity was found. Conclusions Short term rGH for 3 months had a significant effect on mitochondrial function, favourably altered body mass and IGF1 levels, but exercise capacity was unchanged.